1 2 4 7 ⋮ 3 5 8 6 9 1 0
Natural numbers 1 , 2 , 3 , … are placed in a triangle as shown in the above figure. Determine the sum of the numbers in the 2 0 1 6 th row.
Enter your answer as the last three digits of the number.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For better clarity write 1 0 0 8 = 1 0 0 0 + 8 and we know multiplication by thousand we get at least 3 trailing zeroes which will not affect the last 3 digits...
We note that n t h row has n terms and its last term is the n t h triangular number T n = 2 n ( n + 1 ) .
Let a and l be the first and last terms of 2 0 1 6 t h row respectively, then the sum S is given by:
S = 2 2 0 1 6 ( a − l ) Note that a = T 2 0 1 5 + 1 and l = T 2 0 1 6 = 1 0 0 8 ( T 2 0 1 5 + 1 + T 2 0 1 6 ) = 1 0 0 8 ( 2 2 0 1 5 ( 2 0 1 6 ) + 1 + 2 2 0 1 6 ( 2 0 1 7 ) ) = 1 0 0 8 ( 2 0 3 1 1 2 0 + 1 + 2 0 3 3 1 3 6 ) = 4 0 9 6 7 7 1 0 5 6
Sir,you have solved this problem of mine.Can you provide your solution to the problem and see my solution too?
The solution is a little bit lengthy.....
The n t h row has n numbers in it.
Therefore the total numbers till the 2 0 1 5 t h row = 2 2 0 1 5 × 2 0 1 6 = 2 0 3 1 1 2 0
The first number in 2 0 1 6 t h row = 2 0 3 1 1 2 1
The last number in 2 0 1 6 t h row = 2 0 3 1 1 2 1 + 2 0 1 6 = 2 0 3 3 1 3 6
Therefore sum of numbers till the 2 0 1 5 t h row = 2 2 0 3 1 1 2 0 × 2 0 3 1 1 1 2 1 = 2 0 6 2 7 2 5 2 4 2 7 6 0
Therefore sum of numbers till the 2 0 1 6 t h row = 2 2 0 3 3 1 3 6 × 2 0 3 3 1 3 7 = 2 0 6 6 8 2 2 0 1 3 8 1 6
Thus the sum of numbers in the 2 0 1 6 t h row = 2 0 6 6 8 2 2 0 1 3 8 1 6 − 2 0 6 2 7 2 5 2 4 2 7 6 0 = 4 0 9 6 7 7 1 0 5 6
Hence the last three digits are 0 5 6
It's a finite difference sequence.
Problem Loading...
Note Loading...
Set Loading...
Observe the first terms of all the rows. Let their sum be S and n th term be a n .Then
S = S = 1 + 2 + 4 + ⋯ + a n 1 + 2 + ⋯ + a n − 1 + a n
Substracting and rearranging for a n , we get:
a n = 1 + ( 1 + 2 + 3 + ⋯ ( n − 1 ) terms ) = 2 n 2 + n + 1
We can observe that n th row contains n terms, it's first term is a n and common difference is 1 . Thus sum of n th row (An AP) is:
a n + a n + 1 + a n + 2 ⋯ ( n terms ) = 2 n ( 2 ( 2 n 2 + n + 1 ) + ( n − 1 ) )
For n = 2 0 1 6 , this is:
1 0 0 8 ( 2 0 1 6 2 + 1 )
For calculating its last 3 digits, we observe last 3 digits of 2 0 1 6 2 (same as that of 0 1 6 2 ) are 2 5 6 plus one is 2 5 7 multiplied by 8 we get its last three digits as 056
Note :- There is no need to calculate the whole number..